Effects and mechanism of Aβ1−42 on EV-A71 replication - Zhong, Ming; Wang, Huiqiang; Yan, Haiyan; Wu, Shuo; Wang, Kun; Yang, Lu; Cui, Boming; Wu, Mengyuan; Li, Yuhuan (Virology journal, 2022)
Background β-Amyloid (Aβ) protein is a pivotal pathogenetic factor in Alzheimer’s disease (AD). However, increasing evidence suggests that the brain has to continuously produce excessive Aβ to efficaciously prevent pathogenic micro-organism infections, which induces and accelerates the disease process of AD. Meanwhile, Aβ exhibits activity against herpes simplex virus type 1 (HSV-1) and influenza A virus (IAV) replication, but not against other neurotropic viruses. Enterovirus A71 (EV-A71) is the most important neurotropic enterovirus in the post-polio era. Given the limitation of existing research on the relationship between Aβ and other virus infections, this study aimed to investigate the potent activity of Aβ on EV-A71 infection and extended the potential function of Aβ in other unenveloped viruses may be linked to Alzheimer's disease or infectious neurological diseases. Methods Aβ peptides 1–42 are a major pathological factor of senile plaques in Alzheimer’s disease (AD). Thus, we utilized Aβ 1–42 as a test subject to perform our study. The production of monomer Aβ 1–42 and their high-molecular oligomer accumulations in neural cells were detected by immunofluorescence assay, ELISA, or Western blot assay. The inhibitory activity of Aβ 1–42 peptides against EV-A71 in vitro was detected by Western blot analysis or qRT-PCR. The mechanism of Aβ 1–42 against EV-A71 replication was analyzed by time-of-addition assay, attachment inhibition assay, pre-attachment inhibition analysis, viral-penetration inhibition assay, TEM analysis of virus agglutination, and pull-down assay. Results We found that EV-A71 infection induced Aβ production and accumulation in SH-SY5Y cells. We also revealed for the first time that Aβ 1–42 efficiently inhibited the RNA level of EV-A71 VP1, and the protein levels of VP1, VP2, and nonstructural protein 3AB in SH-SY5Y, Vero, and human rhabdomyosarcoma (RD) cells. Mechanistically, we demonstrated that Aβ 1–42 primarily targeted the early stage of EV-A71 entry to inhibit virus replication by binding virus capsid protein VP1 or scavenger receptor class B member 2. Moreover, Aβ 1–42 formed non-enveloped EV-A71 particle aggregates within a certain period and bound to the capsid protein VP1, which partially caused Aβ 1–42 to prevent viruses from infecting cells. Conclusions Our findings unveiled that Aβ 1–42 effectively inhibited nonenveloped EV-A71 by targeting the early phase of an EV-A71 life cycle, thereby extending the potential function of Aβ in other non-envelope viruses linked to infectious neurological diseases.